Improving Knowledge to prevent Hand, Foot, and Mouth Disease (HFMD) or Singapore Flu - Dewi Perwito Sari; Asti Rahayu; Asri Wido Mukti; Noer Febriyanti; Maulivia Idham Choliq; Eka Fitria; Laila Magfiroh Ikwias Suwarso (J.Abdimas: Community Health, 2022)
Hand, foot, and mouth disease (HFMD) is a disease caused by a virus of the genus Enterovirus. HFMD is an infectious disease that often affects children. Although rare, this disease can also affect adults, especially those with low levels of immunity. Symptoms of the flu are a pain in the mouth, and rashes on the hands and feet. HFMD sufferers can transmit the virus through nasal and throat fluids, and feces. Reports in Gorontalo Province showed that there were 38 HFMD cases. Since the beginning of 2022, Gorontalo has also been an increase in HFMD cases in the community. Everyone reported a case of HFMD suspects will be an alert which is a warning of vigilance and needs to be responded to. Intensive efforts are needed to prevent the spread of HFMD from spreading. Seeing this, the service team provided socialization and education about HFMD to increase residents' knowledge so that they could prevent HFMD infection. Based on the results of the HFMD material presentation activities, it is known that there is an increase in knowledge among the residents of Dukuh Menanggal District by 20% in terms of characteristics, symptoms, ways of transmission, and how to prevent HFMD. This increase in knowledge is expected to also increase citizen vigilance and prevent HFMD. Keywords: HFMD; Singapore Flu; Knowledge